Anti-measles potential of selected compounds from uvaria chamae P. beauv: a molecular docking approach (2024)
Measles is an extremely contagious viral infection, reported to be responsible for most global childhood death. Plants have been proven to be very effective against viral diseases with an added advantage of less toxicity. Previous studies have reported the activities of Uvaria chamae extracts against measles virus. This study investigated the in silico anti-measles activities of bioactive compounds from Uvaria Chamae leaves extract. The in silico docking studies were carried out using four compounds isolated from U. chamae (stigmasterol, chrysin, chalcone, and dihydrochalcone) reported in literature. The pharmacokinetic properties of these selected compounds were also evaluated using ADMET studies. The compounds were docked to the measles virus nucleoprotein (PDB ID: 5E4V) and they had binding affinities ranging from -6.4 to -8.2 kcal/mol. Stigmasterol (-8.2 kcal/mol) and Chrysin (-8.0 kcal/mol) showed the greatest affinities for the protein target. These two compounds passed the Lipinski’s Rule of Five for leadlikeness. Stigmastrol and Chrysin showed promising pharmacological properties that indicate that they could be investigated as viable lead candidates for further anti-measles drug development studies.